No Strings Attached to GIs? About a Blind Spot in the (Academic) Discourse on Limitations and Fundamental Rights - Annette Kur (IIC - International Review of Intellectual Property and Competition Law, 2022)
During the last decades, the focus of academic discourse on intellectual property rights~has been on limitations and exceptions, with a strong accent on fundamental rights. However, until now such debates never involved protection of geographical indications under the sui generis system established in the European Union. That is quite remarkable. Already in its current form, the scope of protection granted to such rights is rather broad, as was confirmed and reinforced in the case law of the~Court of Justice of the European Union. According to pending proposals, the scope and ambit of protection shall be strengthened further, without any counterbalance in the form of limitations being envisaged. This opinion argues that turning a blind eye to those developments is no commendable attitude for those concerned about imbalances in intellectual property rights.
Keywords: 340; Geographical indications; Evocation; Fundamental rights; Comparative advertisement; Transit